THORIQOH SEBAGAI SISTEM DAKWAH ANALISIS NILAI-NILAI PEMBELAJARAN DALAM KONSEP THORIQOH - Herdi; Hartono; Meity Suryandari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Tarekat as a medium for da'wah is a method, path, or way to get closer to Allah SWT, in order to achieve the goal of da'wah. The congregation, which is led by a murshid, also provides religious messages to the congregation so that they can become more humble and behave well in society. This research aims to determine the learning values ​​in the concept of thoriqoh in Islamic teachings. This research is library-based research. From the results of research on the media used for preaching in tarekat councils, it can be concluded that in the implementation of dhikr and manaqib there are learning values, invitations and to carry out His commands and avoid His prohibitions. Moreover, in today's life, many people underestimate the congregation.